Makna Modal Usaha Dan Budaya Pada Pengusaha Kerupuk Ikan Di Desa Klangonan Kabupaten Gresik - Dinda, Adinda Ayu Lestari; Agung, Moh. Agung Suriyanto; Anita, Anita Akhiruddin (Jurnal Sains dan Teknologi, 2023)
Abstract−The gap phenomenon in this study is the thought of being able to return business capital derived from existing capital in Klangonan Village. This study aims to examine the meaning of business capital and culture in fish cracker entrepreneurs in Klangonan Village, Gresik Regency.This type of research is qualitative research. The technique used in this study is Purposive Sampling.The data used in this study is primary data.The data validity technique used in this study is member check. Data analysis techniques in this study use interactive models of the model of Miles and Huberman (1984), namely data collection, data reduction, data presentation and conclusions. The results of the analysis of this research data show that there is a meaning of business capital and culture in customs and folkways.Customs are obedience caused by devotion and obligations including inheritance, opportunity, livelihood, gratitude, and responsibility. The folkways perspective is the profit of innovation caused by business success and reciprocity including business continuity, achievement, investment, loyalty, pleasure.